The influence of knowledge of parts of speech on the writing ability of the second-year students at SLTP N 1 Wates in the academic year of 2002/2003 / Supatmiyati - SUPATMIYATI (Universitas Negeri Yogyakarta, 2004)
xvii, 83 hlm. ; 30 cm.